The effect of Copper and Zinc (single and combined) on gill, kidney and muscle of Grass Carp Ctenopharyngodon idella juvenile - Hashem, Amina A.; hasan, Balkes K.; Maki, Rajaa N. (Iraqi Journal of Aquaculture, 2022)
This study was carried out to look for the effect of each copper and zinc on survival of grass carp Ctenopharyngodon idella juvenile and to compare these effects with the combined effects of a mixture of both copper and zinc in same concentration (0.1, 0.5) ppm for 15 days. The results of the study revealed that there is mortality has increased among the juvenile of grass carp with increasing of concentration of the metals and with exposure of them to combination mixture .In addition the bioaccumulation and recovery of both metals were studied in gill, kidney, and muscle. It was reported that the highest bioaccumulation and recovery was in the gill, kidney and muscle respectively.